One Size Does Not Fit All: TFP in the Aftermath of Financial Crises in Three European Countries - Christian Abele; Agnès Bénassy-Quéré; Lionel Fontagné (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyse the impact of both the Global Financial Crisis of 2008 and the European sovereign and banking crisis of 2011-13 on firm-level productivity in France, Italy and Spain. We show that relying on a single break date in 2008 misses both the Eurozone crisis and countries' institutional specificities. Although leverage and financial constraints affect firm-level productivity negatively, high-leverage firms suffer more from financial constraints only in Italy, when they are relatively small or when their debt is of short maturity. These results call for approaches taking into consideration country-level characteristics of financial institutions and time varying financing constraints of the firms, instead of pooling data and adopting a common break date. One size does not fit all when it comes to identifying the impact of financial crises on firm level productivity.
Keywords: E22; E23; E44; D24; 330; total factor productivity; firm-level data; financial constraints; crises